THE EFFECTIVENESS OF DEBATE TECHNIQUE TOWARD THE STUDENTS' CONFIDENCE IN SPEAKING SKILL AT XI GRADE OF SMKN 2 TEMBILAHAN - Malasari, Lorika; Purwanti, Sri Erma (Universitas Wiralodra, 2018)
Confidence is an important thing in speaking because without it speaking skill can not be well and it became one of some problems in speaking skill which faced by the students of SMK Negeri 2 Tembilahan. To solve the problem, the reseacher conducted the experimental research is that quasy experimental design by applying the debate technique. The aim of this research is to know the effectiveness of debate technique on students? confidence in speaking skill. The data collection technique in this research is questionnaire that consists of 20 Close Ended statements using Likert Scale type. The sample of this research is 33 students of XI grade of SMK Negeri 2 Tembilahan as control and experimental class. After getting the data using questionnaire, the reseacher find that debate technique is effective toward students? confidence in speaking skill with the result t-observed is 15,84 while t-table is 2,04 from 5% and 2,75 from 1%. The tobserved score is higher than t-table. Based on the result, H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. It also means that debate technique is effective toward students? confidence in speaking skill at XI grad of SMK Negeri 2 Tembilahan in academic years 2017/2018.